PENINGKATAN MINAT BELAJAR SISWA MELALUI PENERAPAN STRATEGI PROMOSI DIGITAL DALAM PEMBELAJARAN DASAR-DASAR PEMASARAN DI SMK SWASTA JAMBI MEDAN TAHUN PELAJARAN 2025/2026 - Balqis; Ivo Selvia Agusti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve students' learning interest through the implementation of a digital promotion strategy in the Basic Marketing course at SMK Swasta Jambi Medan during the 2025/2026 academic year. The study employed a Classroom Action Research (CAR) design consisting of two cycles, with each cycle including four stages: planning, action, observation, and reflection. The research participants were 30 students of Class X BD. Data were collected through observation, questionnaires, and documentation. The collected data were analyzed using descriptive quantitative analysis by comparing the results obtained during the pre-action stage, Cycle I, and Cycle II based on the predetermined indicators of research success. The findings revealed that the implementation of a digital promotion strategy through the Project-Based Learning (PjBL) model effectively enhanced students' learning interest. During the pre-action stage, students' learning interest was categorized as moderate. Following the implementation of Cycle I, students demonstrated improvements in participation, attention, enthusiasm, and engagement in classroom activities. Further improvements were achieved in Cycle II, where students' learning interest reached the predetermined success criteria. In addition to increasing learning interest, the implementation of the digital promotion strategy also improved students' creativity in developing digital promotional content, self-confidence in presenting their work, collaborative learning skills, and active participation throughout the learning process. Moreover, teachers demonstrated better classroom management by implementing more innovative, interactive, and student-centered learning activities. In conclusion, the implementation of a digital promotion strategy through the Project-Based Learning (PjBL) model is effective in improving students' learning interest in the Basic Marketing course at SMK Swasta Jambi Medan.